Perilaku Seksual Remaja dan Pengaruh Lingkungan Sosial pada Anak-Anak Keluarga Migran dan Nonmigran - Sri Purwatiningsih (Populasi, 2019)
Premarital sexual behavior in adolescents is a social problem that needs attention. Premarital sexual behavior is problematic, because it is not balanced with adequate knowledge of reproductive health, so it often results in unwanted pregnancies among adolescents. The social environment is one of the factors that can be a driving factor for adolescent behavior, but on the other hand the social environment can also make behavioral changes. This article will describe adolescent sexual behavior, both for adolescents from migrant and non-migrant households in the CHAMPSEA (Child Health and Migrant Parents in South East Asia) research area in West Java and East Java. Respondents for this article are young adults with a sample of 429 adolescents from migrant and non-migrant households. The results of the study show that as many as 5.07 percent of unmarried adolescents have had premarital sexual relations, which are carried out both by adolescents from migrant and non-migrant households. Based on gender, premarital sexual behavior is more often carried out by girls than boys. While the age of first premarital sexual intercourse is mostly carried out by adolescents aged 18 years (35 percent), which is different from their perceptions of the age of marriage. Whereas based on the social environment of adolescents, there are 28.74 percent of respondents who have friends who have premarital sexual relations, have premarital sexual relations.